The Problem of Nagorno Karabakh and the Role of Russia and Iran in Solving it 1992 – 1994 - Ahmad, Farhad; Merkhan, Hozan; Abdulrahman, Farooq (Humanities Journal of University of Zakho, 2020)
The significance of this study comes from the fact that it tackles an obscure conflict; the Nagorno-Karabakh conflict. Many great powers and regional countries have interfered in this conflict and tried to find a solution, especially Iran and Russia. They have dealt with the conflict in a way it serves their interests. The researchers have raised some questions and tried to answer them directly or indirectly. The questions include: How did Nagorno-Karabakh conflict start? What are the stages it went through? How did Iran and Russia deal with this conflict? To what extent they succeeded in solving this conflict? The researchers have adopted the model of historical approaches by collecting data related to the subject and analyzed them carefully and accurately. There is no doubt that studies on contemporary history will not be excluded from problems. The biggest problem that faced the researchers was that most of the sources were written in foreign languages such as Arabic, Persian, English and Russian. However, the researchers succeeded, in one way or another, to get benefit from such sources, especially Russian. This, without doubt, gave a privilege to this study.